Six Sigma Dalam Perspektif Akuntansi Manajemen: Peningkatan Manajemen Biaya Strategis dan Pengendalian Kualitas Produk - Damayanti, Alda Putri; Aziza, Nurna (Owner : Riset dan Jurnal Akuntansi, 2024)
The background to this research is that companies that produce snacks often face challenges in managing ever-increasing operational costs and maintaining consistent product quality. In an effort to control increasing production costs, including raw material and labor costs, the company decided to implement Six Sigma as a quality management strategy. Companies face pressure to maintain competitive selling prices while controlling production costs. Variability in the quality of snack products often occurs, which can reduce consumer confidence. The research method uses qualitative and quantitative methods. The types of data used in this research include primary and secondary data, and the data collection methods applied include interviews, observation and documentation. The population that is the focus of the research is the snackproducts. The research sample was selected from a small portion of the population for further analysis. Data analysis was carried out using the Six Sigma method which consists of five stages: define, measure, analyze, improve and control (DMAIC), as well as linear regression analysis. The results of this research provide evidence that Six Sigma can be used as an effective tool to optimize strategic costs and improve product quality. Based on the analysis, the results obtainedare: 1. Machine. Continuous use of the machine results in decreased machine performance. 2. Employees. Suboptimal work results in the product not meeting quality standards. Therefore, this research makes an important contribution in deepening understanding of the application of Six Sigma to achieve cost management goals and improve product quality.